Rehabilitation of patients with venous diseases of the lower limbs: State of the art. (December 2018) - Caggiati, Alberto; De Maeseneer, Marianne; Cavezzi, Attilio; Mosti, Giovanni; Morrison, Nick
Background: To date, no document comprehensively focused on the complex issue of the rehabilitation of chronic venous diseases of the lower limbs. Method: This article overviews and summarizes current strategies concerning venous rehabilitation of lower limbs. Results: Venous rehabilitation is based on four main strategies: (1) lifestyle adaptations and occupational therapies; (2) physical therapies; (3) adapted physical activities; (4) psychological and social support. Rehabilitative protocols must be tailored to the specific needs of each patient, depending on the severity of chronic venous disease and on the location and pattern of venous lesion(s), but also on age, motor deficits, co-morbidities and psychosocial conditions. Conclusions: Venous rehabilitation consists of non-pharmacologic and non-surgical interventions aiming at prevention of venous disease progression and complications, reduction of symptoms and improvement of quality of life. Well-designed clinical trials are required to evaluate the efficacy of the described rehabilitative protocols in influencing the evolution of venous disorders.